Sunny days : the children's television revolution that changed America - Kamp, David (Simon & Schuster, 2020)
"In 1970, in soundstage on Manhattan's Upper West Side, a group of men and women of various ages and races met to finish the first season of a children's TV program. They had identified a social problem: poor children were entering kindergarten without the learning skills of their middle-class counterparts. They hoped, too, that they had identified a solution: to use television to better prepare these disadvantaged kids for school. No one knew then, but this children's TV program would go on to start a cultural revolution. It was called Sesame Street. Sesame Street was part of a larger movement that saw media professionals and thought leaders leveraging their influence to help children learn. A year and a half earlier, Mister Rogers' Neighborhood premiered. Fast on its heels came Schoolhouse Rock!, a video series dreamed up by Madison Avenue admen to teach kids times tables, civics, and grammatical rules, and Free to Be... You and Me, the TV star Marlo Thomas's audacious multi-pronged campaign (it was first a record album, and then a book and a television special) to instill the concept of gender equality in young minds. There was more: programs such as The Electric Company, Fat Albert and the Cosby Kids, ZOOM, and others followed, and captivated young viewers. In Sunny Days, bestselling author David Kamp takes readers behind the scenes to show how these programs made it on air. He draws on hundreds of hours of interviews from the creators and participants of these programs-among them Joan Ganz Cooney, Lloyd Morrisett, Newton Minow, Sonia Manzano, Loretta Long, Bob McGrath, Marlo Thomas, and Rita Moreno-as well as archival research. Kamp explains how these like-minded individuals found their way into television, not as fame- or money-hungry would-be auteurs and stars, but as people who wanted to use TV to help children. This is both a fun and fascinating story, and a masterful work of cultural history. Sunny Days captures a period in children's television where enlightened progressivism prevailed, and shows how this period changed the lives of millions. Nothing had ever happened like this before, Kamp forcefully and eloquently argues, and nothing has ever happened like it since"--